2021
DOI: 10.1111/jar.12869
|View full text |Cite
|
Sign up to set email alerts
|

The role of mobile technology in promoting social inclusion among adults with intellectual disabilities

Abstract: Background: Mobile technology has the potential to assist adults with intellectual disabilities to initiate and maintain social connections in important areas of their lives, such as family, friends and work/volunteering. Method:The present study investigated how specific aspects of mobile device/app use are associated with the social inclusion of people with intellectual disabilities. The study also examined what background attributes were associated with particular patterns of mobile device/app use and socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 31 publications
(78 reference statements)
0
31
0
Order By: Relevance
“…Critical to these opportunities will be ensuring that people with ID and those supporting them possess the digital skills to use technology to their advantage, which is made more difficult because of inaccessible app development (Shpigelman 2018; Martin et al . 2021). This is something that the research team is addressing through the Digi‐ID study, which aims to co‐create accessible digital skills education for people with ID and their carers (Murphy et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Critical to these opportunities will be ensuring that people with ID and those supporting them possess the digital skills to use technology to their advantage, which is made more difficult because of inaccessible app development (Shpigelman 2018; Martin et al . 2021). This is something that the research team is addressing through the Digi‐ID study, which aims to co‐create accessible digital skills education for people with ID and their carers (Murphy et al .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Martin et al . (2021) found that self‐determined use of mobile technology and apps was associated with improved social inclusion among adults with ID (mean age 42), as was more frequent use and use of more devices and apps. Chiner et al .…”
Section: Introductionmentioning
confidence: 99%
“…Integral, complex care -The main problem is to join different public and private initiatives in the complex network of interaction for all people including rural and less developed areas and all households, including first of all those living alone, and researchers are advising to check all aspets including housing (Arundel & Ronald 2021). Researchers in many countries have found and analysed research results in good practice on that (Martin, et al, 2021;Pernegger, 2021). The The significance of cooperation and solidarity between people and generations becomes more clear during crises.…”
Section: Interaction Of Society Members In Local Communities As the F...mentioning
confidence: 99%
“…However, people can be further excluded if too much weight is given to perceived online risks—which might lead to gatekeeping and restrictions of access—but not enough effort is put into equipping people with skills to manage this risk and learn to navigate the online world (D. Chadwick, 2019 ). Other studies identify control over internet use by staff and/or families and safeguarding concerns, access to WIFI, and costs as barriers inhibiting digital engagement (Caton & Chapman, 2016 ; Alfredsson Ågren et al, 2020a ; Martin et al, 2021 ). It has further been suggested that some researchers assume people with learning disabilities are not able to use technology (Seale et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%